Quality Analysis of Management Information Systems Drug Inventory in The Pharmacy Warehouse Dr. Suyudi Paciran Lamongan Hospital - Nabela Pandu Winata; Annora Marsha Sunparta; Amirul Amalia; M.Arif Saifuddin; Madekhan; Nuryati; M. Ganda Saputra (Jurnal Surya, 2024)
Introduction: Management Information System (SIM) is one of the most important assets in the era of globalization. The role of technology makes information processing easier because processing is very necessary so that the information produced can be useful for its users, especially in pharmaceutical warehouse drug inventory. The results of the initial survey through interviews showed that there were problems at dr. Suyudi like the discrepancy between the data on drug stock inventory in the computer inventory system and the drug stock in the pharmaceutical warehouse. The purpose of the research is to analyze human resources, SPO, Data, Software, Hardware of drug inventory management information systems in pharmaceutical warehouses. Methods: Descriptive qualitative research design with purposive sampling technique. Data collection instruments are in the form of interview guidelines, observation and document review. Results: The results of human resources research (can run smoothly if supported by human resources who have adequate quality and capacity). SPO (SPO is available but the applicable SPO has not been carried out optimally by pharmacists). Data (the existence of data can help officers in minimizing errors and losses). Software (can help ease the work because the supply of drug data is already stored on the computer but the obstacle is often errors and slow). Hardware (important to support the smooth flow of drug supply activities through the hospital SIM application and facilities are in accordance with standards). Conclusion: Based on the results of the study, it is expected that the management will evaluate the supply of drugs in the pharmaceutical warehouse in using the hospital driver's license.